Investigation of Direct A-GPS Positioning for Hybrid E-OTD/GNSS - Liew, S. C.; Tan, K. G.; Lim, T. S. (2006)
Assisted Global Positioning System (A-GPS) is intended to offer positioning capability with improved service availability and accuracy gain to areas such as street canyon in major cities, and even into indoor environment in some cases. This paper studies the positioning determination based on hybrid E-OTD/GNSS system developed in EMILY project. This study proposes another way of position calculation which is referred as direct method ill this paper. This is an easier and simpler method as compared to conventional approach based on Taylor series expansion which is referred as approximate method in this paper. The. proposed method requires additional ranging information which can be easily sought from surrounding base station (BTS). The obtained results show that the proposed direct method can achieve better accuracy as compared to approximate method.